Microrobots: A new era in ocular drug delivery - Fusco, Stefano; Ullrich, Franziska; Pokki, Juho; Chatzipirpiridis, George; Ozkale, Berna; Sivaraman, Kartik M.; Ergeneman, Olgac; Pane, Salvador; Nelson, Bradley J. (Expert Opinion on Drug Delivery, 2014)
Introduction: Ocular microrobots have the potential to change the way in which we treat a variety of diseases at the anterior and the posterior segments of the eye. Wireless manipulation and positioning of drug delivery magnetic millimeter and submillimeter platforms into the eye constitute a potential route for minimally invasive targeted therapy. However, the field is still in its infancy and faces challenges related to the fabrication, control an interaction with complex biological environments.Areas covered: This review briefly introduces the complex anatomy and physiology of the eye, which renders limitations to the current treatments of ocular diseases. The topical administration of eye drops, intravitreal injections and drug delivery implants is briefly mentioned together with their drawbacks. The authors also analyze the minimally invasive microrobotic approach as an alternative method and report the recent advancements in the fabrication, control, manipulation and drug delivery.Expert opinion: Although microrobotics is a young field, a significant amount of work has been developed to face different challenges related to the minimally invasive manipulation of microdevices in the eye. Current research is already at the state of in vivo testing for systems and their biocompatibility. It is expected that the general concepts acquired will soon be applied for specific interventions, especially for posterior eye pathologies.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Eye; Functional coatings; Magnetic manipulation; Microrobots